Diferentes frações inspiradas de oxigênio e hiperinsuflação mecânica na aspiração endotraqueal aberta : impacto na oxigenação e ventilação pulmonar - Vianna, Jacqueline Rodrigues de Freitas (Universidade Federal de São Carlos, 2015)
Endotracheal suction (ES) in mechanically ventilated patients is required for maintaining a patent airway. Open circuit endotracheal suction (OCES) may cause greater damage to respiratory mechanics and gas exchange. There is little evidence about the impact of the use of oxygen concentrations below 100% and the expiratory pressure-zero end expiratory pressure (PEEP-ZEEP) technique at increasing oxygenation and maintaining adequate ventilation during the OCES. In addition studies were not found concerning need or not of hyperoxygenation associated with the PEEP- ZEEP and the effectiveness of isolated hyperoxygenation with oxygen concentration 20% above the baseline, thus justifying the studies of this thesis. Study I aimed to evaluate whether the 20% oxygen concentration of inspired oxygen fraction (FiO2) above the baseline avoids hypoxemia compared the offer to 100% and determine the impact of OCES on pulmonary ventilation in critical patients on mechanical ventilatory support. This randomized crossover study involved 68 patients in an adult intensive care unit (ICU), intubated, mechanically ventilated and placed in the two intervention sequences: Hyperoxygenation using 20% above FiO2 (FiO2 20%) and Hyperoxygenation using 100% FiO2(FiO2 100%). Hyperoxygenation was applied 1 min before each of the 5 ES and 1 min after OCES. The studied variables were measured pre, immediately after and 1min, 2 min and 30 min after OCES. There was a significant intra-group increase in immediate post FiO2 20% and 100% on peripheral oxygen saturation (SpO2), carbon dioxide (CO 2) exhaled at the end of expiration (ETCO2), partial pressure of CO2 in the mixed expired air (PeCO2 ), heart rate (HR), mean arterial pressure (MAP), and in the tidal volume of CO2 (VtCO2) only for the FiO2 20%. Intergroup in the immediate post in VtCO 2, ETCO2 and SpO 2 restoring the pre intervention values 30 min after measurement. It was concluded that an oxygen concentration of 20% above baseline FiO2 for patients with need of prior offer  60% effectively avoided hypoxemia and volumetric capnography analysis confirms that changes in pulmonary ventilation in OCES in critical patients are transient and reversible within 30 min. These findings also support the implementation of Study II which aimed to verify behavior of peripheral oxygen saturation (SpO2) and exhaled end- expiratory CO2 (ETCO2), for the OCES procedure, using PEEP-ZEEP baseline FiO2 versus PEEP-ZEEP hyperoxygenation using 20% above FiO 2. This randomized crossover study involved 38 patients in an ICU, intubated, mechanically ventilated and placed in the two intervention sequences: PEEP-ZEEP with baseline FiO2 (PEEP-ZEEP FiO2 baseline) and PEEP-ZEEP with 20% above FiO2 (PEEP-ZEEP hyperoxygenation). Hyperoxygenation was applied 1 min before each of the 5 procedures and 1 min after OCES. PEEP-ZEEP with 3 series before each of the 5 ES. The studied variables were measured pre, immediately after and one, two and 30 min after OCES. There was significant increase in SpO2 on PEEP-ZEEP hyperoxygenation, with maintenance of adequate levels on PEEP-ZEEP FiO2 baseline no change in ETCO2 in both interventions. Significant difference was found in intergroup SpO2 post 1 min of hyperoxygenation, immediate post, post 1and 2 min of OCES. Significant difference was found in intergroup SpO2 post 1 min of hyperoxygenation, immediate post, post 1 and 2 min of OCES. It was concluded that the PEEP-ZEEP technique, when well indicated, associated or not to hyperoxygenation is effective to avoided the fall of SpO2 and maintain levels of ETCO2, minimizing the impairment in the ventilation caused by OCES.
Keywords: Sucção; Ventilação mecânica; Modalidades de fisioterapia; Oxigênio; Capnografia; Suctioning; Mechanical ventilation; Pulmonary ventilation; Respiratory mechanics; Capnography; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL